SUN-LB58 Repeated Once-Daily Administration of the Non-Hormonal Neurokinin 1,3 Receptor Antagonist NT-814 Reduces LH, Estradiol and Progesterone in Healthy Women - Dhillo, Waljit Singh (J Endocr Soc, 2020)
Introduction: Uterine fibroids (UF) affect up to 25% of women and endometriosis (EM) 10% of women worldwide. An ideal therapy would lower estradiol concentrations to reduce hormonal drive to the endometrium and myometrium, but not to the levels which cause the hot flashes and bone loss associated with current treatments. A target estradiol range of 110-180 pmol/L has been proposed(1). GnRH secretion is modulated by neurokinin B (NKB) acting at the NK3 receptor via hypothalamic neurons expressing kisspeptin, NKB & dynorphin (KNDy neurons). In addition, Substance P acting at the NK1 receptor may also stimulate reproductive hormone release. We hypothesised that NT-814, a dual NK1,3 receptor antagonist, would reduce GnRH release and hence LH, estradiol and progesterone levels in women. This preliminary clinical study in healthy pre-menopausal women evaluated this hypothesis. Methods: We undertook a randomized, single-blind, placebo-controlled study. 32 healthy women attended for 2 consecutive menstrual cycles. In each cycle blood samples were taken on days 3/4, 9/10, 15/16 and 21/22 to measure serum sex hormone concentrations. No treatment was given in cycle 1 (baseline). During cycle 2, participants received placebo or one of three doses of NT-814 once per day; 40mg, 80mg or 120mg (n=8 per group) for up to 21 days. Results: Compared to placebo, NT-814 reduced LH, estradiol and progesterone concentrations in a dose-related manner. The median changes in average LH (IU/L) during cycle 2 compared to cycle 1 were: placebo, 0.16; 40mg, -0.13; 80mg, -0.46; 120mg, -0.58. Median change in average estradiol (pmol/L) in cycle 2 was: placebo, -16.5; 40mg, -9.3; 80mg, -92.1; 120mg, -141.4. The median changes in progesterone (nmol/L) on day 21/22 in cycle 2 compared to cycle 1 were: placebo, 3.2; 40mg, 8.0; 80mg, -5.7; 120mg, -19.4. The reductions in estradiol and progesterone with 120 mg NT-814 were significant (p=0.038 & p=0.046, respectively). There were no clear changes in FSH concentrations. Of note, in women treated with 120mg NT-814, the average estradiol level reduced from 310.8 pmol/L in cycle 1 to 179.8 pmol/L in cycle 2. Cycle length was extended by at least 6 days in 5 of 8 women receiving the 120 mg dose. NT-814 was well tolerated; no participant experienced hot flashes during treatment. Conclusions: Once-daily administration of the non-hormonal NK1,3 receptor antagonist NT-814 reduced serum LH, estradiol and progesterone in healthy women in a dose-related manner without causing vasomotor symptoms. The 120 mg dose of NT-814 lowered estradiol levels to potentially ideal levels for UF and EM treatment. These preliminary data support further studies with NT-814 to establish its efficacy and safety in treating patients with these hormone driven disorders. References: (1)Barbieri RL Am J Obstet Gynaecol 1992 166 740-5.